CORPORATE SOCIAL RESPONSIBILITY EXPENDITURE DAN KINERJA PERUSAHAAN - Celine Florencia wedjaja; Rizky Eriandani (RISTANSI: Riset Akuntansi, 2022)
This study aims to analyze the effect of Corporate Social Responsibility Expenditure on company performance and the effect of firm-specific economic variables on Corporate Social Responsibility Expenditure. The research population is all companies listed on the Indonesia Stock Exchange (IDX) except for the banking sector and other financial institutions from 2016 to 2019. Based on the purposive sampling method, 372 samples were obtained. The data is taken from the company's financial statements and tested using the multiple linear regression method. The results of this study indicate that CSR expenditure has a significant effect on ROA, but has no significant effect on CFO. Other findings show that CFO, size, and PM have a significant effect on CSR expenditure. Meanwhile, cash, ATO, and leverage have no significant effect on CSR expenditure.